Heretics of Dune - Herbert, Frank (New York : Berkley, 2019)
Several millenia after the 3500 year rule of the God Emperor Leto II, various forces contend for power, and the freedom of humanity rests on avoiding Leto's grand design.
Booklist
Voice of Youth Advocates (V.O.Y.A.)
Wilson's Senior High School
Booklist, August 1997
Voice of Youth Advocates (V.O.Y.A.), July 1996
Wilson's Senior High School, November 1997
Keywords: Life on other planets -- Fiction; Life on other planets -- Fiction; Science fiction